Vancomycin for the Induction and Maintenance of Remission in Biologics Refractory Patient with Ulcerative Colitis and Primary Sclerosing Cholangitis Post-Liver and Bone Marrow Transplantation - Mohammad Shehab; Anwar Almajdi; Mohammed Alotaibi; Maen Almattooq (Case Reports in Gastroenterology)
Introduction: Inflammatory bowel disease-primary sclerosing cholangitis (IBD-PSC) is a unique disease entity that has very poorly understood pathogenesis and unique clinical presentation. Patients with this disease may eventually require liver transplantation as there is no current curative treatment for PSC to halt disease progression for liver failure. Thirty percent of patients with IBD may experience recurrence despite being on immunosuppression. Few studies have shown that vancomycin has been used as a salvage treatment for patients with refractory ulcerative colitis (UC) exacerbation refractory to conventional and biological agents. In this report, we discuss the case of 25-year-old female with a prior history of sickle cell disease (SCD), UC, post-liver transplant secondary to PSC, who developed UC exacerbation refractory to conventional therapies and most biological agents and was induced and maintained in remission with oral vancomycin (OV). Case Presentation: This is the case of 25-year-old female with a history of SCD, UC, and primary sclerosing cholangitis (PSC) who developed liver cirrhosis and underwent liver transplantation. Prior to liver transplantation, she had recurrent exacerbations of UC, refractory conventional therapies, and most biological agents. Post-liver transplantation, she developed another UC flare despite being treated with ustekinumab. OV 125 mg four times daily was used as salvage therapy post-liver transplantation to control her UC. Conclusion: This report supports the use of OV in patient with SCD who had UC exacerbation refractory to conventional and biological agents.